(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
In 1335, upon its surrender to Azzone Visconti, the city of Vercelli produced two crucial documents: the first, well-known to historiography, is the record of the city council assembly on September 26th, formalizing the decision to surrender; the second, unpublished until now, is a deed drawn up directly in the lord’s palace in Milan on October 1st, registering the transfer of power. Analysing this latter document goes beyond mere erudition, allowing us to observe the still-evolving dynamics, in the mid-14th century, concerning the development of nascent regional states and the written and diplomatic practices that underpinned their formation.